1986
DOI: 10.1172/jci112377
|View full text |Cite
|
Sign up to set email alerts
|

Glomerular injury in uninephrectomized spontaneously hypertensive rats. A consequence of glomerular capillary hypertension.

Abstract: Micropuncture and/or morphologic studies were performed in intact Wistar-Kyoto rats (WKY) (group 0) intact spontaneously hypertensive rats (SHR) (groups 1 and 5), uninephrectomized (UNX) WKY (groups 2 and 6), and UNX SHR (groups 3 and 4, 7 and 8). UNX was performed when rats were 5 wk of age. Groups 0-4 were observed for 34 wk after which whole kidney clearance and morphologic studies were performed. Groups 5-8 underwent micropuncture study at 10 wk of age. Groups 4 and 8 were fed a diet containing 6% protein.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
78
0

Year Published

1991
1991
2008
2008

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(84 citation statements)
references
References 38 publications
(37 reference statements)
6
78
0
Order By: Relevance
“…28 The development of diabetic renal injury was accelerated by uninephrectomy, which has been shown to increase glomerular capillary hydraulic pressure and plasma flow rate in nondiabetic rats. 29 This study confirmed that in SHR a high salt intake prevents the hypotensive effect of chronic ACE inhibitor therapy. 1617 Treatment with ramipril produced a fall in systemic systolic blood pressure only when administered to rats receiving a normal salt intake.…”
Section: Discussionsupporting
confidence: 78%
“…28 The development of diabetic renal injury was accelerated by uninephrectomy, which has been shown to increase glomerular capillary hydraulic pressure and plasma flow rate in nondiabetic rats. 29 This study confirmed that in SHR a high salt intake prevents the hypotensive effect of chronic ACE inhibitor therapy. 1617 Treatment with ramipril produced a fall in systemic systolic blood pressure only when administered to rats receiving a normal salt intake.…”
Section: Discussionsupporting
confidence: 78%
“…In the previous experimental studies in different hypertensive models, it was found that increased glomerular pressure might be involved in the development of glomerulosclerosis which was associated with a compensatory glomerular hyperfiltration [4,5,18]. In this study, we observed that the systolic blood pressure of FGS/Nga was slightly higher than CBA/N and RFM/ Nga mice.…”
Section: Discussionsupporting
confidence: 53%
“…This action could provide reverse glomerular capillary hypertension and additional amelioration of renal injury. 27,28 To assess this possibility of bradykinin-induced renal protection, we simultaneously administered the bradykinin antagonist icatibant (HOE140) with enalapril. However, the icatibant (HOE140) only blunted the systemic antihypertensive effects of enalapril and failed to attenuate the enalapril-induced effects of renoprotection and the progression of glomerulosclerosis.…”
Section: Discussionmentioning
confidence: 99%